What do we know about biological nitrogen fixation in insects? Evidence and implications for the insect and the ecosystem. (17th June 2019) - Bar‐Shmuel, Nitsan; Behar, Adi; Segoli, Michal
Abstract: Many insects feed on a low‐nitrogen diet, and the origin of their nitrogen supply is poorly understood. It has been hypothesized that some insects rely on nitrogen‐fixing bacteria (diazotrophs) to supplement their diets. Nitrogen fixation by diazotrophs has been extensively studied and convincingly demonstrated in termites, while evidence for the occurrence and role of nitrogen fixation in the diet of other insects is less conclusive. Here, we summarize the methods to detect nitrogen fixation in insects and review the available evidence for its occurrence (focusing on insects other than termites). We distinguish between three aspects of nitrogen fixation investigations: (i) detecting the presence of potential diazotrophs; (ii) detecting the activity of the nitrogen‐fixing enzyme; and (iii) detecting the assimilation of fixed nitrogen into the insect tissues. We show that although evidence from investigations of the first aspect reveals ample opportunities for interactions with potential diazotrophs in a variety of insects, demonstrations of actual biological nitrogen fixation and the assimilation of fixed nitrogen are restricted to very few insect groups, including wood‐feeding beetles, fruit flies, leafcutter ants, and a wood wasp. We then discuss potential implications for the insect's fitness and for the ecosystem as a whole. We suggest that combining these multiple approaches is crucial for the study of nitrogen fixation in insects, and argue that further demonstrations are desperately needed in order to determine the relative importance of diazotrophs for insect diet and fitness, as well as to evaluate their overall impact on the ecosystem.